Assessing the Effects of the 2023 Turkish Earthquakes on Mental Health in Lebanon: A Cross-sectional Study - Hojeij, Moussa; El Khatib, Dalida; Salameh, Pascale (International Journal of Clinical Research, 2024)
Background: On the 6 of February 2023, an earthquake registering 7.8 on the Richter Scale hit the South and center of Turkey, as well as the North and West Syria. Subsequently, another seismic event with a magnitude of 7.5 ensued a few hours later. Two weeks later, a new earthquake of 6.4 magnitude shook both countries again. These two events left behind more than 50000 deaths and a lot of damage, both economically and psychologically, which affected the Lebanese population. Aim: This study evaluates the adverse effects of these earthquakes on the mental health of people in Lebanon. Methods: This is a cross-sectional study conducted between 6 March, and 23 March 2023, using an online survey. The questionnaire was divided into 4 sections: demographics, the mental health of participants, anxiety before the earthquakes, and anxiety after the earthquakes using the Lebanese Anxiety Scale- to differentiate between healthy and anxious participants. Results: The study involves 670 Lebanese participants aged 18 or above. Anxiety proportion rose post-earthquakes. Pre-earthquakes, anxiety risk factors included female gender, younger age, Beirut residency, mental health issues, and medication use; these factors also significantly raised anxiety after earthquakes. Conclusion: This study demonstrates a remarkable escalation in anxiety proportion following the earthquakes. Pre-existing risk factors such as female gender, younger age, Beirut residency, mental health issues, and medication use for symptom relief exhibited a heightened association with anxiety after the tectonic events. These findings deepen the importance of targeted interventions to address the psychological impact of earthquakes on vulnerable populations.